Review of Synthesis Cu2ZnSnS4 Using Ball-Milling Method as Thin Film Solar Cell Absorber Layer - Maghfirani Aulia Rachman; Eka Cahya Prima; Andhy Setiawan (Universitas Sultan Ageng Tirtayasa, 2023)
CZTS (Cu2ZnSnS4) is a readily available, cost-effective, and non-toxic material that uses as a material for absorbing coatings on solar cells. This study aims to examine making CZTS using the Ball-milling method. This method uses a cylindrical grinding machine to reduce coarse materials into more delicate fabrics. The CZTS synthesis process using ball-milling produces better results than other non-sputtering methods. In addition, the synthesis of CZTS using ball-milling can increase the yield of better solar cells. However, in ball-milling, there are still shortcomings, one of which is the presence of heterogeneous elements after the synthesis.